(3GdfUjMI GdcGajI def NUg Gddg HGdYGajIs - (3CMeO Hf eMeO Hf YjSi,J (B899 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3hHYO aEf GdfUjMI ef GdEjeGf hGdJMbjb HgG hCYXe GdfGS LgdkG ef Lgd faSg s
(3BNQgG (B:s
(3Gddge EfG fJhSd Edjc Hge aEfge CMHhc heG CMHhc MJi CMHHJge aMHc EjGge hUdhG Edi MHc hfMf de fUd Edi MHge ajc EdG HNWfG efc aJee dfG hPdc eY GdYGajI GdTGedI GdJGeI GdcGedI MJi fdbGc jG CQMef GdQGMejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI HgG JQejes
(3hjcGO jchf NWgG eWehSkG s
(3hYdjgG MhGTi hTQhMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs